2020
DOI: 10.3168/jds.2020-18268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maintaining eucalcemia following immunoactivation in lactating Holstein dairy cows

Abstract: Periparturient hypocalcemia is a common metabolic disorder and it is ostensibly associated with negative health and production outcomes. Acute infection also markedly decreases circulating Ca, but the reasons for and consequences of it on physiological and immunological parameters are unknown. Objectives were to evaluate the effects of maintaining eucalcemia on production, metabolic, and immune variables following an intravenous lipopolysaccharide (LPS) challenge. Twelve multiparous lactating Holstein cows (71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 84 publications
(136 reference statements)
3
33
1
1
Order By: Relevance
“…Perhaps one of the most intriguing results of our study was the markedly different pattern in circulating LBP in response to LPS. In contrast to previous LPS infusion studies, which demonstrate a continuous increase in LBP for ~24 h (Horst et al, 2018(Horst et al, , 2019a(Horst et al, , 2020, we observed an abrupt decrease below baseline values at 12 h after LPS infusion. Interestingly, this decrease occurred concurrently with the NEFA plateau and peak TG concentrations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Perhaps one of the most intriguing results of our study was the markedly different pattern in circulating LBP in response to LPS. In contrast to previous LPS infusion studies, which demonstrate a continuous increase in LBP for ~24 h (Horst et al, 2018(Horst et al, , 2019a(Horst et al, , 2020, we observed an abrupt decrease below baseline values at 12 h after LPS infusion. Interestingly, this decrease occurred concurrently with the NEFA plateau and peak TG concentrations.…”
Section: Discussioncontrasting
confidence: 99%
“…Across species, several well-conserved metabolic alterations are employed during immune activation to meet the energetic requirements of leukocytes (Filkins, 1978;Lanza-Jacoby et al, 1998;McGuinness, 2005), and these have been described in detail in our previous ruminant publications (Kvidera et al, 2017;Horst et al, 2018Horst et al, , 2019aHorst et al, ,b, 2020. In brief, a biphasic response in circulating glucose is observed in response to LPS with an initial period of hyperglycemia followed by hypoglycemia (Kvidera et al, 2017;Horst et al, 2018Horst et al, , 2019a.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work demonstrates the calcium 'cost' of mounting an inflammatory response to an acute LPS challenge. Using a model analogous to Kvidera et al (2017) for glucose, Horst et al, (2018) showed that in the 12 h after challenge with LPS, blood calcium concentration was reduced by 32%, and maintenance of eucalcemia during that time required infusion of 12 g of Ca, or somewhat more than the typical deficit (8 to 10 g) in a cow recumbent with milk fever. Subclinical hypocalcemia is highly prevalent among periparturient cows and is associated with increased risk of displaced abomasum (Chapinal et al, 2011) and milk production losses (Chapinal et al, 2012) and increased culling risk in early lactation (Roberts et al, 2012).…”
Section: Calciummentioning
confidence: 99%
“…Using an induction model of acute inflammation, Kvidera et al (2017) demonstrated that euglycemia could be maintained in lactating cows only when exogenous glucose supply was more than 1 kg within 720 min after an LPS challenge. Intravenous administration of LPS resulted in hypocalcemia in dairy cows (Horst et al, 2020). Daily injections of tumor necrosis factor-α (TNF-α; a proinflammatory cytokine) over a 7-d period (i.e., repeated inflammatory insults) in cows in late lactation increased liver triglyceride accumulation (Bradford et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Parturition is a high-risk period for immune challenges, during which considerable adaptations in metabolism occur to support lactation. In a lipopolysaccharide challenge model using dairy cows, immune activation has been shown to decrease circulating Ca (Horst et al, 2020), suggesting that an acute inflammatory process can negatively affect the metabolic adaptation of dairy cows in the transition period. Using the liver activity index as the main parameter, Bertoni et al (2008) found that cows with higher indexes had increased concentrations of Ca and Mg in the postpartum period; this could be suggestive of an improved metabolic adaptation process.…”
mentioning
confidence: 99%